Survey on Retention Protocols Among Turkish Orthodontists - Aylin Paşaoğlu; Işıl Aras; Ali Mert; Aynur Aras (Galenos Yayinevi, 2016)
Objective:The purpose of this study was to identify general retention protocols practiced by Turkish orthodontist and to compare the results obtained with those of similar studies in Western countries.Methods The Web-based survey consisted of 29 questions: 3 to identify the demographic characteristics of the participants and 26 to examine how orthodontists manage the retention phase. Data was interpreted by descriptive statistical methods such as the median test, the Mann-Whitney U-test and logistic regression analysis.Results:The survey return rate was 73.8%. Pretreatment malocclusion status (87%), oral hygiene status (78%), and presence of third molars (63%) were reported to be the most important factors in determining the type of retainer. Bonded retainers, either alone (29% in maxilla and 34% in mandible) or supplemented with vacuum-formed retainers (27% in maxilla and 32% in mandible) were the most commonly used type of retainer. The preference for lifelong retention varied from 7% to 19%. Female orthodontists scheduled the first appointment after debonding sooner than male orthodontists (p<0.05). Orthodontists working in universities scheduled first appointments later than orthodontists working in private practices (p<0.05).Conclusion:Turkish orthodontists still give importance to the third molars in their retention protocols, contrary to what is suggested in the current literature, and lifetime retention is rarely preferred as compared to other countries.